The factored form of x^4 - 5x^2 + 4 has to be determined.

x^4 - 5x^2 + 4

= x^4 - 4x^2 - x^2 + 4

= x^2(x^2 - 4) - 1(x^2 - 4)

= (x^2 - 1)(x^2 - 4)

= (x - 1)(x + 1)(x - 2)(x + 2)

**The factored form of x^4 - 5x^2 + 4 = (x - 1)(x + 1)(x - 2)(x + 2)**

The factored form of x^4 - 5x^2 + 4 has to be determined.

x^4 - 5x^2 + 4

= x^4 - 4x^2 - x^2 + 4

= x^2(x^2 - 4) - 1(x^2 - 4)

= (x^2 - 1)(x^2 - 4)

= (x - 1)(x + 1)(x - 2)(x + 2)

**The factored form of x^4 - 5x^2 + 4 = (x - 1)(x + 1)(x - 2)(x + 2)**